PIWI‐Interacting RNA HAAPIR Regulates Cardiomyocyte Death After Myocardial Infarction by Promoting NAT10‐Mediated ac4C Acetylation of Tfec mRNA. Issue 8 (9th February 2022) - Wang, Kai; Zhou, Lu‐Yu; Liu, Fang; Lin, Liang; Ju, Jie; Tian, Peng‐Chao; Liu, Cui‐Yun; Li, Xin‐Min; Chen, Xin‐Zhe; Wang, Tao; Wang, Fei; Wang, Shao‐Cong; et al.
Abstract: PIWI‐interacting RNAs (piRNAs) are abundantly expressed in heart. However, their functions and molecular mechanisms during myocardial infarction remain unknown. Here, a heart‐apoptosis‐associated piRNA (HAAPIR), which regulates cardiomyocyte apoptosis by targeting N ‐acetyltransferase 10 (NAT10)‐mediated N4‐acetylcytidine (ac 4 C) acetylation of transcription factor EC (Tfec) mRNA transcript, is identified. HAAPIR deletion attenuates ischemia/reperfusion induced myocardial infarction and ameliorate cardiac function compared to WT mice. Mechanistically, HAAPIR directly interacts with NAT10 and enhances ac 4 C acetylation of Tfec mRNA transcript, which increases Tfec expression. TFEC can further upregulate the transcription of BCL2‐interacting killer (Bik), a pro‐apoptotic factor, which results in the accumulation of Bik and progression of cardiomyocyte apoptosis. The findings reveal that piRNA‐mediated ac 4 C acetylation mechanism is involved in the regulation of cardiomyocyte apoptosis. HAAPIR‐NAT10‐TFEC‐BIK signaling axis can be potential target for the reduction of myocardial injury caused by cardiomyocyte apoptosis in ischemia heart diseases. Abstract : Heart‐apoptosis‐associated piRNA (HAAPIR) promotes cardiomyocyte apoptosis by regulating RNA N4‐acetylcytidine (ac4C) modifications. Mechanistically, HAAPIR promotes Tfec mRNA acetylation modifications by recruiting NAT10. This results in Tfec mRNA more stable and increases its translation efficiency, and increased expression of transcription factor TFEC, which, in turn promotes the transcription of Bik, a pro‐apoptotic factor that participates in the apoptosis process.